Functional insights into immunoglobulin superfamily proteins in invertebrate neurobiology and immunity - Hongyu Li; Hongyu Li; Yijie Zhang; Yunhuan Zhu; Qingzhi Zhao; Jialu Xu; Xianwei Li; Ling Zhao; Hairun Li; Mingcheng Liu; Yuncheng Qian; Xiaofen Zhang; et al. (Frontiers in Immunology)
The Immunoglobulin Superfamily (IgSF) represents a vital protein family widely distributed in animal genomes, encompassing multifunctional proteins with immunoglobulin-like domains, including immunoglobulins. These proteins play pivotal roles in various biological processes, such as development, differentiation, adhesion, activation, regulation, and signal transduction. While the functions of IgSF in vertebrates are relatively well understood, their roles in invertebrates remain underexplored. This review aims to comprehensively summarize the functions and mechanisms of IgSF in invertebrates, focusing on arthropods, mollusks, and other primitive phyla. In arthropods, research on IgSF has primarily emphasized its roles in the nervous system, especially in axonal and synaptic regulation, and its critical functions in the immune system. Studies in mollusks have predominantly highlighted the immunological functions of IgSF in pathogen recognition, clearance responses, and signal transduction. In contrast, research on protozoa and platyhelminths has mainly focused on identifying IgSF molecules, with relatively limited insights into their functional roles. In sponges, IgSF is primarily associated with cell adhesion and intercellular recognition. By exploring the genetic and protein structural diversity of IgSF in invertebrates, this review reveals their multifunctionality and complexity in biological systems. It not only enhances our understanding of the roles of IgSF in invertebrates but also lays the groundwork for future studies on their potential applications in evolutionary biology and disease models.